Tracer Study Berbasis Teknologi Informasi dan Psikologi - Edi Supratman; Leon Abdillah; Dwi Hurriyati; Chairul Mukmin (Jurnal Pengabdian kepada Masyarakat Bina Darma, 2022)
Advances in Information Technology (IT) have provided many conveniences in various fields, such as government, business, and education. The global COVID-19 pandemic that has hit the world since 2019 has made many human activities limited due to a number of rules from health protocols. The tracer study process that was previously carried out conventionally has shifted to the digital mode by utilizing various information technology applications. The tracer study implementation process involves 3 (three) main stages, namely (1) the concept and instrument development stage; (2) Stages of collecting questionnaire data, and (3) Stages of data analysis and writing of tracer study reports. The Community Service Team (PKM) provides counseling to schools to empower a number of IT-based applications and psychological approaches for tracer studies. By using Google Forms, Facebook Groups, and WhatsApp Groups, tracer studies can still be carried out even though there are social limitations due to the pandemic. The results of the tracer study are very useful for the school to find out the distribution of alumni, and input from alumni regarding the various obstacles experienced by alumni.